2019
DOI: 10.1177/1103308818817603
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Young People Engaged in Climate Activism: The Potential of Collectivizing Despair and Hope

Abstract: Hope takes on particular significance at this historical moment, which is defined by the prospect of a climate-altered future. Young people (aged 18–29) from climate action groups in New Zealand were interviewed about how they perceived the future. Deploying a unique combination of conceptual tools and in-depth analysis of a small set of interviews, I explore young New Zealanders’ complex relationships with despair and hope. Paulo Freire claimed his despair as a young man ‘educated’ what emerged as hope. I ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 34 publications
5
79
0
8
Order By: Relevance
“…Norgaard's study showed that anxiety and other difficult emotions were caused on one hand by changes in geophysical environment and, on the other hand, by pressures to social worlds. Afterwards, this notion of how social and ecological factors become intertwined has been shown in many empirical studies which have included reflections about eco-anxiety and climate anxiety [15,43,[54][55][56][57][58]. Numerous different social factors shape people's experiences of eco-anxiety.…”
Section: Social and Political Sciences: Anxiety As Related To Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Norgaard's study showed that anxiety and other difficult emotions were caused on one hand by changes in geophysical environment and, on the other hand, by pressures to social worlds. Afterwards, this notion of how social and ecological factors become intertwined has been shown in many empirical studies which have included reflections about eco-anxiety and climate anxiety [15,43,[54][55][56][57][58]. Numerous different social factors shape people's experiences of eco-anxiety.…”
Section: Social and Political Sciences: Anxiety As Related To Changesmentioning
confidence: 99%
“…A highly charged social issue in industrialized countries is the decreasing childbirth rate. During the last years of the 2010s, a growing number of people told that eco-anxiety, and especially climate anxiety, is an important reason for their reluctance to have children [15] (p. 7) [43] (p. 22) [13,20]. Organizations or movements such as Conceivable Future in the USA and BirthStrike in the UK have provided platforms for people who have these kinds of thoughts.…”
Section: Social and Political Sciences: Anxiety As Related To Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…She showed that an IBC approach detracted young people from deeper engagement with the difficult work of thinking about the underlying causes of climate change, including the emotional work involved in imagining different and new alternatives to current socio-economic and socio-political realities. Another New Zealand-based study of climate activists also reported high levels of despair, burnout and eco-anxiety, but found hope through recognising the strength that collective, rather than individual, responses that climate change could bring (Nairn 2019). These studies suggest that researchers need to pay far more attention to the imaginations of young activists themselves and allow possibilities to see collective hope and solidarity, not only despair and the need to embed this in theoretical and methodological frameworks.…”
Section: Explainsmentioning
confidence: 98%
“…This common approach focuses on an individual's own actions to reduce environmental and climate impacts -such as recycling, using reusable bags, reducing carbon footprint, eating less meat and so on. While this has some merits, it has been found to be closely associated with growing levels of 'eco-anxiety', guilt and despair amongst children, young people and climate activists (Christensen 2019;Lawton 2019;Nairn 2019;Thomas et al 2019). These prevailing and individualising anxieties make their way into how we research, with a good example being the Wahlström and colleagues (2019) report which overlooked the joyful and hopeful aspects of the climate strikes, focusing instead on anxiety, fear and hopelessness due to the narrow framing of the methodology (Bowman 2019).…”
Section: Focus On Individual Behavioural Changementioning
confidence: 99%